In situ investigations of the phase change behaviour of tungsten oxide nanostructures. Issue 4 (25th April 2018) - Thummavichai, Kunyapat; Wang, Nannan; Xu, Fang; Rance, Graham; Xia, Yongda; Zhu, Yanqiu
Abstract : This study uses two in situ techniques to investigate the geometry and phase change behaviour of bundled ultrathin W18 O49 nanowires and WO3 nanoparticles. The in situ X-ray diffraction (XRD) results have shown that the phase transition of WO3 nanoparticles occurs in sequence from monoclinic (room temperature) → orthorhombic (350°C) → tetragonal (800°C), akin to bulk WO3 ; however, W18 O49 nanowires remain stable as the monoclinic phase up to 500°C, after which a complete oxidation to WO3 and transformation to the orthorhombic β-phase at 550°C is observed. The in situ Raman spectroscopy investigations have revealed the Raman peak downshifts as the temperature increases, and have identified the 187.6 cm −1 as the fingerprint band for the phase transition from γ- to β-phase of the WO3 nanoparticle. Furthermore, WO3 nanoparticles exhibit the γ- to β-phase conversion at 275°C, which is about 75°C lower than the relaxation temperature of 350°C for the monoclinic γ-W18 O49 nanowires. These new fundamental understandings on the phase transition behaviour offer important guidance for the design and development of tungsten oxide-based nanodevices by defining their allowed operating conditions.